An Idea to design a system to detect Air pollution in different area - Rajput, Hansa; Barde, Snehlata (International Journal of Computer Sciences and Engineering, 2025)
Our society has many challenges related to the environment, one of them is air pollution. There are many causes to increase the air pollution percentage in different area some of them are transportation, industrialization and constructions. It creates unhealthy atmosphere. Many people are suffering from many deceases invoked from the pollution. So we planned to design an air pollution monitoring system which indicates the polluted air amount in the environment. It will help to identify the polluted areas.